Re-engagement with the United Kingdom, a study of non-state actors in Zimbabwe’s foreign policy since 2017 - Mutumbwa, T. B. (BUSE, 2020)
This research aims to understand why Zimbabwe’s re-engagement foreign policy of 2017 encountered challenges from a non-state actor perspective. After the dramatic end of President Mugabe’s rule, the incoming administration re-oriented its foreign policy thrust by engaging Britain and Western states. In spite of government’s efforts to re-engage Britain, it appeared that attempts to mend relations the former colonial power and its allies failed to gain traction. In trying to understand why this policy shift encountered challenges, this research examined the role and impact of civil society organisations CSOs in Zimbabwe’s foreign policy. In conducting this research, the researcher employed qualitative research methods since the research problem required the opinions of CSOs and entities involved in the Zimbabwe foreign making process. Interviews and document analysis were the main methods employed to collect data in this research. The primary area that this study was conducted was in Harare, Zimbabwe. This research established that certain lobbying activities CSOs negatively impacted Zimbabwe’s re-engagement programme with the West. It was discovered that the damaging activities of CSOs especially on social media affected diplomatic efforts by the government of Zimbabwe to re-establish its bilateral relations and multilateral relations with the Western bloc. Additionally, it was also discovered that other factors such as the issue of human rights and the failure to implement reforms stalled re-engagement process. One of the key recommendations from this investigation submits that government must fix its internal challenges with CSOs if it wishes to make progress on the diplomatic front with Western states
Keywords: Re-engagement; Foreign policy